SOSIALISASI PEMBUATAN BIOAKTIVATOR DARI GEDEBONG PISANG DI DESA MERAH MATA - Ahmad Zikri; Rima Daniar; Iriani Reka Septiana; Merly Andria Monica; Aghnia Nessa; Muhammad Abdillah Assyauqi (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
The composting process, which is the decomposition of organic matter into humus, can be significantly accelerated by the addition of bioactivators. Bioactivators contain high concentrations of specific microorganisms that can accelerate the decomposition of complex organic materials such as cellulose, lignin, and protein. Banana peel waste, often considered organic waste, is rich in nutrients that can be utilized by these microorganisms. In Merah Mata Village, the abundant availability of banana peels has not been optimally utilized. This community service program aims to empower local communities with the knowledge and technical skills to produce bioactivators from banana peels. The process of making bioactivators involves the fermentation of banana peels with superior microorganisms that have been isolated. The resulting bioactivator is expected to improve soil quality by increasing organic matter content, improving soil structure, and providing nutrients for plants. Thus, the productivity of local agriculture can be increased sustainably. In addition, the utilization of banana peels as raw materials for bioactivators also contributes to reducing the volume of organic waste and better environmental management.